Comparison of ex vivo and in vivo micro‐computed tomography of rat tibia at different scanning settings. Issue 8 (12th October 2016) - Longo, Amanda B.; Salmon, Phil L.; Ward, Wendy E.
ABSTRACT: The parameters of a micro‐computed tomography (μCT) scan, including whether a bone is imaged in vivo or ex vivo, determine the quality of the resulting image. In turn, this impacts the accuracy of the trabecular and cortical outcomes. The absolute impact of μCT scanning at different voxel sizes and whether the sample is imaged in vivo or ex vivo on the morphological outcomes of the proximal tibia in the rat is unknown. The right proximal tibia of 6‐month‐old Sham‐control and ovariectomized (OVX) rats ( n  = 8/group) was scanned using μCT (SkyScan 1176, Bruker, Kontich, Belgium) using three sets of parameters (9 μm ex vivo, 18 μm ex vivo, 18 μm in vivo) to compare the trabecular and cortical outcomes. Regardless of scan protocols, differences between Sham and OVX groups were observed as expected. At a voxel size of 18 μm, scanning in vivo or ex vivo had no effect on any of the outcomes measured. However, compared to a 9 μm voxel size scan, imaging at 18 μm resulted in significant underestimation of the connectivity density ( p  < 0.05) of the trabecular bone and a significant overestimation ( p  < 0.05) of the trabecular indices (trabecular thickness, degree of anisotropy) and of the cortical indices (cortical bone area, cortical area fraction, cortical thickness) in both Sham and OVX rats. These results suggest the benefit to scanning the proximal tibia of rats at a voxel size as low as 9 μm, although considerations must be made for the increased acquisition time, anesthesia, animal welfare, and radiation exposure associated with lower voxel size in vivo scanning. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1690–1698, 2017.